A Comparative Study of Recycling of Used Engine Oil Using Extraction by Composite Solvent, Single Solvent, and Acid Treatment Methods. (11th July 2013) - Abro, Rashid; Chen, Xiaochun; Harijan, Khanji; Dhakan, Zulifqar A.; Ammar, Muhammad
Abstract : Engine oils are made from crude oil and its derivatives by mixing of certain other chemicals (additives) for improving their certain properties. Lubricating oil is used to lubricate moving parts of engine, reducing friction, protecting against wear, and removing contaminants from the engine, act as a cleaning agent, and act as an anticorrosion and cooling agent. This research effort focuses on comparative study of re-refined engine oils by extraction of composite solvent, single solvent, and acid treatment methods. Composite solvent was made up of butanol-propane and butanone; propane was used as single solvent. Different properties of refined oil and waste oil were analyzed, such as cloud and pour point, flash point, specific gravity, ash content, viscosity, moisture ratio and acid value. On the basis of experimental work, it was found that the iron contamination decreased from 50 ppm to 13 ppm for composite solvent; for propane solvent it decreased up to 30 ppm and 15 ppm for acid treatment. Results from the flash point, pour point, viscosity, specific gravity, and ash percentage were improved at different degrees, but the best results were seen by using the composite solvent with having drawback of expensiveness.